Explaining racial/ethnic and socioeconomic differences in COVID protective behavior - Raymond Swisher; Ginny Garcia-Alexander; Lynne Cossman; Drew Schaefer (Elsevier, 2022)
COVID-19 has had a disproportionate impact on Black, Hispanic, and lower socioeconomic status communities. Using data from the Community, Health and Politics Study (CHAPS 2021), collected in the midst of the pandemic, we examine differences in COVID-19 health promotion behavior (i.e., avoiding large gatherings, mask wearing, and vaccination status) across racial, ethnic, and socioeconomic status subgroups of the population. Moreover, we examine the degree to which observed differences are robust to controls for other health-related disparities, such as access to health insurance, underlying health conditions, personal exposure to COVID-19 (i.e., own diagnoses, knowing persons who have died from COVID-19), and perceived COVID-19 threat. Findings are consistent with arguments proposed by fundamental cause theory and disease stage theory as they indicate fewer differences on the basis of socioeconomic status or race and ethnicity for masking and social distancing, which may be thought of as less effective measures. In contrast, disparities were prominent in vaccination outcomes. Specifically, racial and ethnic minorities, those with lower levels of education, and those with lower incomes had lower odds of vaccination, after controlling for covariates. Private insurance and older age were also associated with higher odds of vaccination. Higher perceived threat of COVID-19 increased the likelihood of all protective behaviors. Our findings suggest that the need for ongoing efforts to increase vaccination uptake in socially disadvantaged communities.